2014
DOI: 10.1177/1040638713515480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different serological methods to detect antibodies specific to Neospora caninum in bovine and canine sera

Abstract: Neospora caninum is an apicomplexan parasite responsible for paresis in dogs and abortion in cattle worldwide. Dogs serve as a definitive host, while cattle serve as intermediate host. Many different methods have been developed to detect specific antibodies present in cattle and dog serum. In the present study, the dense granule protein NcGRA6 was incorporated in a latex beads agglutination test (LAT), and compared to other serological methods, including enzyme-linked immunosorbent assay, the direct agglutinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A previous study in Algeria indicated that the N. caninum seroprevalence in cattle was 19.6% using IFAT ( 19 ). On the other hand, ELISA gave fewer positive results than IFAT ( 20 ). Therefore, our results were consistent with the previous ones.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in Algeria indicated that the N. caninum seroprevalence in cattle was 19.6% using IFAT ( 19 ). On the other hand, ELISA gave fewer positive results than IFAT ( 20 ). Therefore, our results were consistent with the previous ones.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of antibodies against N. caninum has been undertaken worldwide in dogs [ 25 , 28 , 29 , 34 ]. The reference method for this detection is the IFAT [ 5 , 8 , 28 ]. A 1:50 cut-off in IFAT has been recommended and commonly used for canine sera [ 25 , 28 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These methods include the indirect immunofluorescence test (IFAT), Neospora-agglutination test (NAT), enzyme-linked immunosorbent assay (ELISA), or immunoblotting, among others (Dubey and Schares, 2006;Dubey et al, 2007;Wapenaar et al, 2007). New techniques described recently include a dense granule protein (NcGRA6) incorporated in a latex beads agglutination test (LAT) (Ghalmi et al, 2014) or a disperse dye immunoassay technique for detection of antibodies against N. caninum (Selahi et al, 2013). Most of these techniques have been validated and have proved to be quite sensitive and specific for the detection of infection in cattle (von Blumroeder et al, 2004).…”
Section: Serological Tests In Diagnosing Bovine Neosporosismentioning
confidence: 98%